Evaluation of Regional Taste Function in Healthy Thai Subjects Using Standard Suprathreshold Tastants - Tharatham Phonmanee; Naruphon Sastranuruk; Paraya Assanasen; Kawita Atipas (Siriraj Medical Journal)
Objective: To evaluate regional taste function in normal Thai subjects using standard suprathreshold tastants.